2018
DOI: 10.1074/jbc.ra118.004549
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells induce distinct modes of cancer cell death: Discrimination, quantification, and modulation of apoptosis, necrosis, and mixed forms

Abstract: Immune therapy of cancer is among the most promising recent advances in medicine. Whether the immune system can keep cancer in check depends on, among other factors, the efficiency of immune cells to recognize and eliminate cancer cells. We describe a time-resolved single-cell assay that reports the quality, quantity, and kinetics of target cell death induced by single primary human natural killer (NK) cells. The assay reveals that single NK cells induce cancer cell death by apoptosis and necrosis but also by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 46 publications
(58 reference statements)
5
101
0
Order By: Relevance
“…We confirmed that chelating Ca 2+ by EGTA abrogated both granzyme-B-dependent apoptosis and necrosis induced by primary NK cells 15 in the cell line panel that we studied (data not shown). However, we did not observe high Ca 2+ concentration shifted NK cell killing to the necrosis mode, as reported by Backes et al [13]. Increasing Ca 2+ concentration up to 3.5 mM did not enhance necrotic killing of SMMC-7721 or U-2 OS cells.…”
Section: Dynamics Of the Actomyocin Network Upon Formation Of The Nk-supporting
confidence: 83%
See 2 more Smart Citations
“…We confirmed that chelating Ca 2+ by EGTA abrogated both granzyme-B-dependent apoptosis and necrosis induced by primary NK cells 15 in the cell line panel that we studied (data not shown). However, we did not observe high Ca 2+ concentration shifted NK cell killing to the necrosis mode, as reported by Backes et al [13]. Increasing Ca 2+ concentration up to 3.5 mM did not enhance necrotic killing of SMMC-7721 or U-2 OS cells.…”
Section: Dynamics Of the Actomyocin Network Upon Formation Of The Nk-supporting
confidence: 83%
“…Upon recognition of abnormal cell targets, NK cells can elicit direct target cell death by 4 three main mechanisms, i.e., lytic granule-mediated apoptosis, death ligand-mediated apoptosis and necrosis [11][12][13]. Lytic granule-mediated cytotoxicity is considered the principal cytotoxic pathway of NK cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to an induction of pyroptosis mediated by activated caspase-3 as previously reported ( Rogers et al, 2017 ; Wang et al, 2017 ). Alternatively, this could be caused by the amount of perforin and GrzB released by the NK cells ( Backes et al, 2018 ). Although it was recently shown that the degranulation of as little as two to four granules is sufficient to cause cell death, it was also reported that NK cells release ∼10% of their total granules in a single killing event ( Gwalani and Orange, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…NK cells kill infected and transformed cells via a variety of mechanisms, including the delivery of lytic granules loaded with proteases and pore-forming proteins such as granzymes and perforin, release of cytokines such as tumor necrosis factor alpha (TNFα) and interferon gamma (IFNγ), upregulation of FASL and TNF-related apoptosis-inducing ligand (TRAIL) and by antibody-dependent cellular cytotoxicity (ADCC) [15][16][17][18][19]. There are multiple steps between NK cell: target cell engagement and cell killing, with receptor-ligand interactions thought to be the initiating step in the formation of an immunological synapse (IS) ( Figure 1A,B) [20,21].…”
Section: Introductionmentioning
confidence: 99%